MAKANAN LUNAK MEMBAHAYAKAN KESEHATAN GIGI - Ni Made Sirat (Jurusan Keperawatan Gigi Poltekkes kemenkes Denpasar, 2013)
Food is not only necessary for growth and health, but also for physical and mental development. Food given day-a day to be such, the support optimal growth and to prevent deficiency disease, prevent poisoning, and also help prevent diseases as an adult. The purpose of this paper is to provide an overview about the dangers of soft foods on dental health. The relationship between the consumtion of carbohidrates with caries dentis nothing to do with the formulations of plaque on the tooth surface. Plaque is made up of food debris attached in between the teeth. Plaque will eventually be covered with bacteria that can alter the pH of mouth down to pH 4.5. In the circumtances, the structure would dissolve tooth enamel (enamel is insoluble at pH 5.41). Consumtion of refined sugar ( candy, chocolate, caramel) frequently, will lead to a permanent acidity of the oral cavity, so that more email dissolved. Severe demage to the email, called caries dentis. Carbohydrates such as sucrose (table sugar, beet sugar, cane sugar) has the effect of cariogenic higher than carbohidrates such as fructose (fruit sugar), glucose (grape sugar) and maltose (malt sugar). While complex carbohidrates such as starch (starch) cariogenic no effectat all. Based on the above discussion it can be concluded that one of plaque causes of dental caries and periodontal disease. Soft foods containing carbohydrates especially sucrose accelerates plaque formation types. To prevent caries dentis advised to avoid or reduse consumption of soft foods, especially foods that contain sucrose software